2021
DOI: 10.3399/bjgpo.2021.0129
|View full text |Cite
|
Sign up to set email alerts
|

Safer Prescribing and Care for the Elderly (SPACE): a cluster randomised controlled trial in general practice

Abstract: BackgroundSafer prescribing in general practice may help to decrease preventable adverse drug events (ADE) and related hospitalisations.AimTo test effect of SPACE on high-risk prescribing of non-steroidal anti-inflammatory drugs (NSAIDs) and/or antiplatelet medicines and related hospitalisations.Design & settingPragmatic cluster randomised controlled trial in general practice. Participants were patients at increased risk of ADEs from NSAIDs and/or antiplatelet medicines at baseline. SPACE comprises automat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…This process evaluation used mixed methods to help understand implementation of the SPACE intervention in general practice and the limited effect of the intervention, adding to the knowledge gained from the pilot study and qualitative interviews. [3][4][5] Recruitment into the trial was challenging. Time pressures and poor remuneration remain major barriers to GPs participating in research, but it was also bad timing that a non-trial safer prescribing initiative targeting the same prescribing topic was introduced at the same time.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This process evaluation used mixed methods to help understand implementation of the SPACE intervention in general practice and the limited effect of the intervention, adding to the knowledge gained from the pilot study and qualitative interviews. [3][4][5] Recruitment into the trial was challenging. Time pressures and poor remuneration remain major barriers to GPs participating in research, but it was also bad timing that a non-trial safer prescribing initiative targeting the same prescribing topic was introduced at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…The SPACE trial was conducted in 39 general practices with 21 867 participants identified as at increased risk of experiencing gastrointestinal, renal or cardiac ADEs from nonsteroidal anti-inflammatory or anti-platelet medications at baseline, of whom 1479 (6.8%) had received high-risk prescribing. 3 Of the 39 practices, 20 were allocated to the intervention group, including 100 GPs and 613 participants with high-risk prescribing at baseline. All practices had electronic medical records and used practice management systems compatible with the trial system for a remote electronic search of the practice database.…”
Section: Study Populationmentioning
confidence: 99%
See 3 more Smart Citations